An ANALYSIS OF DEMAND FOR FRUITS AMONG HOUSEHOLDS IN KWARA STATE, NIGERIA.: Demand for Fruits among Households in Kwara state, Nigeria. - Shehu, A. S.; Aishat, O. S. (BADEGGI JOURNAL OF AGRICULTURAL RESEARCH AND ENVIRONMENT, 2023)
Fruits and vegetables’ consumption is germane in obtaining food and nutritional security but, its consumption is far below the minimum nutritive recommendation in Nigeria. Thus, this study analyzed the demand for fruits among households in Kwara State. A multistage random sampling technique was used to select 300 respondents. A well-structured interview schedule was used to collect information on socio-economic features, types of fruits consumed, frequency of consumption, consumption patterns, demand for fruits and factors influencing the demand for fruits in Kwara. Descriptive statistics and Linear Approach Almost Ideal Demand System (LA-AIDS) were used to achieve the research objectives. Majority (80%) of the respondents were males with a mean age and monthly income of 51 years and N56, 381 respectively. The study revealed that mango is the most frequently consumed fruit with mean score of 3.29, this was narrowly followed by cashew (2.97), Banana (2.69), Watermelon (2.66), Orange (2.59), Cherry (2.12), while Pineapple (2.06) is the least frequently consumed fruit. The consumption pattern indicated that respondents earn an average income of N56, 227 and they spent most (49.79%) of their incomes on food and least (8.48%) on fruits. LA-AIDS showed positive and significant cross parameter. The demand for fruits was influenced by perception, level of income, and storage facilities with the mean score of 3.69, 3.65, and 3.65 respectively. The study therefore recommends the need to change the perception of the people through aggressive sensitization on the benefits inherent in fruits consumption. Policies and strategies towards making efficient storage facilities available to households to enhance bulk purchases of fruits should be encouraged.